Perceived differential vulnerability and climate change-related hazards in informal settlements in Accra, Ghana: re-thinking vulnerability to climate change in urban areas. Issue 4 (3rd April 2023) - Adams, Ishmael; Ghosh, S.; Runeson, G.
ABSTRACT: Urbanisation in developing countries has co-evolved with exposure to hazards among the urban poor. Yet, current understandings of hazard vulnerability are context-specific and limiting for shedding light on perceived vulnerability to climate change in the context of informal urbanisation. The overall perception of informal dwellers on the causative and local factors that underly the processes of informal urbanisation and their hazard exposure and consequent vulnerability tends to receive less attention. Using Accra as a case and applying mixed methods, this paper analyses informal residents' perceived vulnerability to hazards. A total of 582 households' surveys and 3 institutional key informant interviews were conducted. The paper argues that hazard vulnerability in informal settlements is spatially differentiated and differentially perceived. The main factor associated with respondents' perceived vulnerability was "threats of eviction". Examination of informal dwellers' hazard responses will improve our understanding of the influence of their perceptions on hazard responses in the context of informal urbanisation.